MEANING OF CARING FOR RELATIVES OF PERSONS WITH FRIEDREICH ATAXIA (Fiep Bulletin - online, 2013)
The Friedreich Ataxia is considered a rare, chronic-degenerative disease who often evolves to death in adulthood. The study aimed to understand the importance of caring for family members of individuals with Friedreich Ataxia. Qualitative research from oral history. The two subjects, mother and sister, refer significant changes in lifestyle, concern about not maintain care and becoming ill, difficulty in bringing them to the hospital, and also waiting for professionals with “goodwill" to serve them. As a supportive condition, they show an exacerbation religious belief and the search for supernatural forces to relieve the suffering caused by the care process. The home visitation was an experience and a support strategy. We note the wide gap that separates the real situation experienced by the family when facing the institution and its "competent" professionals in the care of their health needs.
Keywords: Friedreich Ataxia; Family Relations; Comprehensive Health Care